Increase in energy efficiency of a steel billet reheating furnace by heat balance study and process improvement - Koushik Chakravarty; Sunil Kumar (Energy Reports, 2020)
Steel is the inevitable material for the infrastructure and has the strategic importance for the growth of the country. Iron and steel making industry is one of the most energy-intensive industries, with 5% of the worlds total energy consumption. Therefore, it is required to develop suitable and efficient energy management during various processing in steel plants. Both academic and industrial research is going on worldwide to increase the energy efficiency for reducing the energy cost imparted due to application of reheating furnaces in various metallurgical process. Reheating furnaces are widely used in the Iron and Steel Industry to reheat the semi-finished products like slabs or billets to the rolling temperature at 1250°C. Reheating furnace is one of the major energy consuming equipment for rolling mills. It is also important to optimize the fuel consumption in this reheating process to avoid any overheating of the steel material which may result in the poor quality of the final product. The aim of this investigation is to conduct an analysis to explore possibilities for the improvement in the energy efficiency of an operating natural gas fired reheating furnace. Some important efficiency improvement measurements were conducted and the fuel efficiency improved by 21% along with the productivity increased by 11%. As a result of these investigations, some energy saving opportunities were ascertained. These measures culminate in the overall projected fiscal savings of INR 264 million/year. Our study not only provides efficient solutions to steel industry for proper energy utilization, but also offers ways for the self-innovation of other academic and laboratory scale research activity.
Keywords: 330; Energy efficiency; Fuel consumption; Heat balance; Reheating furnace; Thermocouple; Thermography